2012
DOI: 10.1007/s10815-012-9712-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human cumulus cells on the maturation and developmental potential of immature oocytes in ICSI cycles

Abstract: The presence of cumulus cells surrounding the immature oocytes during IVM before ICSI had no influence on nuclear maturation and fertilization, but leads to better subsequent embryonic development. This is perhaps mediated by an improvement in cytoplasmic maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…Subsequently, IVF or intracytoplasmic sperm injection (ICSI) was performed according to the routine of our reproductive center. Similarly, embryo quality on day 3 was evaluated according to the criteria previously described (17). Available embryos were those scored as R5, and discarded embryos were those that scored as <5.…”
Section: Ivf Embryo Culture and Embryo Evaluationmentioning
confidence: 99%
“…Subsequently, IVF or intracytoplasmic sperm injection (ICSI) was performed according to the routine of our reproductive center. Similarly, embryo quality on day 3 was evaluated according to the criteria previously described (17). Available embryos were those scored as R5, and discarded embryos were those that scored as <5.…”
Section: Ivf Embryo Culture and Embryo Evaluationmentioning
confidence: 99%
“…In ovarian follicles, cumulus cells and GCs communicate with oocytes to support proper oocyte growth [10], which is important for fertilization and embryonic development [11]. A previous study found that human cumulus cells do not affect oocyte nuclear maturation, but instead affect cytoplasmic maturation and subsequent embryonic development [12]. Another study showed that inhibition of cumulus cell apoptosis improves oocyte quality and the embryo development rate [13].…”
Section: Introductionmentioning
confidence: 99%
“…ICSI was performed only in cases of severe male factor infertility or previous fertilization failure. Embryo was evaluated and scored 72 h after fertilization according to the previously described criteria [19]. Blastocyst was evaluated and scored according to the criteria presented by Gardner and Schoolcraft (1999) [20].…”
Section: Cos Protocol and Ivf/ Intracytoplasmic Sperm Injection (Icsimentioning
confidence: 99%